Pengaturan Pengenaan Pajak dalam Peralihan Hak Atas Tanah dan Bangunan - I Putu Surya Wadi Putra; Ketut Kasta Arya Wijaya; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2022)
Indonesia is a country consisting of sharing tribes, races, and cultures where each community has their own thoughts and understanding to live their lives. In carrying out his life society is no stranger to the name of human rights where human behavior should not interfere with the rights. In the present many people invest in land and buildings where in the future will generate a lot of profits because each nominal issued today will double in the next few years can be likened to as if we are saving for our future. The consequences of land and building ownership certainly cannot be separated by the greater taxes, the land and wealth that a person has the greater as well as the tax deposit that must be deposited to the government. With regard to taxes on land and buildings the government has its rules on Law No. 20 of 2000 on Duties on Land and Building Rights Acquisition. If the people who have assets are certainly no stranger to taxes and if they do not pay it will be taxed in the form of fines.